COMMENTS PUBLIC AFFAIRS DIVISION FOR THE STAFF PRESENTATION AS THE MEETING OF INSTITUTE BOARD OF DIRECTORS PUBLIC SMOKING ISSUE (Tufts Archival Research Center, 2007)
Confidential; Comments on the Public Smoking Issue for the Tobacco Institute Annual Meeting in December, 1989. Emphasizes the importance of minimizing the negative stigma surrounding secondhand smoke. Encourages lobbyists and consultants to concentrate efforts on preventing workplace smoking bans and instead focus legislation on indoor air quality.